2019
DOI: 10.3390/s19153422
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Classification for Assessing the Degree of Stenosis and Blood Flow Volume at Arteriovenous Fistulas of Hemodialysis Patients Using a New Photoplethysmography Sensor Device

Abstract: The classifier of support vector machine (SVM) learning for assessing the quality of arteriovenous fistulae (AVFs) in hemodialysis (HD) patients using a new photoplethysmography (PPG) sensor device is presented in this work. In clinical practice, there are two important indices for assessing the quality of AVF: the blood flow volume (BFV) and the degree of stenosis (DOS). In hospitals, the BFV and DOS of AVFs are nowadays assessed using an ultrasound Doppler machine, which is bulky, expensive, hard to use, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The study results showed that SVM offered good effectiveness. Moreover, Chiang et al [25] used the data of a novel PPG and the classification method of SVM to evaluate the quality of dialysis patients’ AV fistula, involving the blood flow volume and degree of stenosis. The experimental data showed that with PPG data, the SVM-based prediction of fistula obstruction could reach a precision of 87.84% and the prediction of blood flow volume could reach a precision of 88.61%.…”
Section: Related Workmentioning
confidence: 99%
“…The study results showed that SVM offered good effectiveness. Moreover, Chiang et al [25] used the data of a novel PPG and the classification method of SVM to evaluate the quality of dialysis patients’ AV fistula, involving the blood flow volume and degree of stenosis. The experimental data showed that with PPG data, the SVM-based prediction of fistula obstruction could reach a precision of 87.84% and the prediction of blood flow volume could reach a precision of 88.61%.…”
Section: Related Workmentioning
confidence: 99%
“…The PPG signals are composed of two components: DC and alternating component (AC) as shown in Figure 2 [15]. The AC corresponds to the variation of blood volume in synchronization with heartbeat pulse, and it is used to measure heart rate.…”
Section: Photoplethysmographymentioning
confidence: 99%
“…The AC pulse signal is superimposed on the DC signal, where more than 90% of the pulse amplitude is contributed by the DC component [58]. Both the AC and DC waveforms are extracted using suitable filters and amplifiers, and later the AC waveforms are used for subsequent pulse analysis in a software tool like Matlab.…”
Section: Working Principle Of the Ppg Sensormentioning
confidence: 99%